Sustainability handbook - Blackburn, William R. (London, 2007)
The Sustainability Handbook covers all the challenges, complexities and benefits of sustainability for businesses, governments and other organizations. It provides a blueprint for how organizations can reach or exceed economic, social and environmental excellence. It offers a host of practical approaches and tools including a model sustainability policy for organizations, summaries of sustainability codes and tips on selecting them, an extensive collection of metrics and a wealth of supplementary reference material. This is the essential reference for every organization in pursuit of sustainability.
Keywords: Sustainabilty